Relationship between Body Mass Index and Intraocular Pressure in Diabetic and Hypertensive Adults - Mazhar-ul-Hassan, Darshan Kumar, Farnaz Siddiqui, Saba Alkhairy (Pakistan Journal of Ophthalmology, 2016)
Purpose: To Evaluate the relationship between body mass index and intraocular pressure in Diabetic and Hypertensive adults presenting to the Out Patient department of Dow International Medical College. Study Design: Descriptive Cross – sectional study. Place and Duration of Study: Department of Ophthalmology, Dow University Hospital (Ojha Campus) of Dow International Medical College, Dow University of Health Sciences, Karachi, Pakistan from 15 March 2015 to 15 April 2015. Material and Methods: This study done in the Department of Ophthalmology, Dow University Hospital (Ojha campus) of Dow International Medical College, Dow University of health sciences, Karachi, Pakistan from 15 March 2015 to 15 April 2015. 101 patients were Included in the study group who were known Diabetics with or without Hypertension. Height, weight, blood pressure and intraocular pressure (IOP) were recorded in these patients. IOP was measured using the Goldmann applanation tonometer. The correlation between Body Mass Index (BMI) and IOP was calculated and the statistical analysis was done by SPSS version 21. Results: 101 patients were examined, 45 were males and 56 were females. Mean BMI was 29.86 ± 5.87 in patients having diabetes with hypertension and 27.49 ± 4.99 in only diabetic patients. The mean IOP was found to be 16.34 ± 0.34 in diabetic and hypertensive patients and 15.98 ± 0.43 in diabetic patients. BMI was significantly correlated with IOP in both diabetic with or without hypertensive adults. Conclusion: These results show a correlation between BMI and IOP in both diabetic patients with or without hypertension. Increase in BMI is strongly associated with increase in IOP. Key words: Body Mass Index, Diabetes, Hypertension, Intraocular Pressure, Glaucoma.